PROBLEMAS EN LA EVALUACIÓN DE LA COMPETENCIA DISCURSIVA EN INGLÉS COMO L2 - Chacón Beltrán, Rubén (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract Nowadays, language testing is considered a fundamental component in foreign language teaching and learning. In this paper, some of the most representative features of language testing are described and special attention is given to the question of language test validity. Some well-known language-testing institutions use the native speaker (NS) as a stakeholder to evaluate the overall level in the foreign language, without taking into account the feasibility of such a concept. In this regard, some arguments are presented in order to demonstrate the ambivalence of the notion of “native speaker” in language learning evaluation. Particular attention is paid to international language-testing standards that, although well-known and widely used, may not be as appropriate as they are assumed to be. Some suggestions are made for the field of bilingualism studies.